MENGUKUR KINERJA KEUANGAN PT MATAHARI DEPARTMENT STORE TBK DENGAN ANALISIS LAPORAN KEUANGAN - Dimas Dwi Setiawan; Cucu Hayati; Hanifah Hanifah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
PT Matahari Department Store Tbk is a retail company that started its business in 1958, by the end of 2022 the company owned and operated 148 outlets. PT Matahari Department Store Tbk sells a wide range of products such as children's clothing, youth clothing, adult clothing, shoes, bags, accessories and make up. The purpose of this research is to measure the financial performance of PT Matahari Department Store Tbk for three years from 2020 to 2022. The quantitative descriptive approach method is the research method used in this research. Liquidity ratios, solvency ratios, and profitability ratios are ratios used as data analysis techniques. Based on the results of the calculation of the ratio that has been done, it shows that PT Matahari Department Store Tbk has poor financial performance. These findings highlight the need for the company to address these issues and implement strategies to improve its financial performance in the future.